2022
DOI: 10.1038/s41598-022-19397-w
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic CD8+ T cells may be drivers of tissue destruction in Sjögren’s syndrome

Abstract: Sjögren’s syndrome is a chronic autoimmune disorder whose pathogenesis is poorly understood and that lacks effective therapies. Detailed quantitative and spatial analyses of tissues affected by Sjögren’s syndrome were undertaken, including the quantitation of the frequency of selected cell–cell interactions in the disease milieu. Quantitative analyses of CD4+ T cell subsets and of CD8+ T cells in the labial salivary glands from untreated patients with primary Sjögren’s syndrome revealed that activated CD8+ cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…The greater Th1 and Th2 signatures in SGs of Stim1/2 Foxp3 mice compared to their Cre-negative controls are consistent with altered Th1 and Th2 cytokine levels reported in patients with SjD 44,[54][55][56][57][58][64][65][66] .…”
Section: Loss Of Soce In Treg Cells Promotes Th1-and Th2-mediated Inf...supporting
confidence: 77%
“…The greater Th1 and Th2 signatures in SGs of Stim1/2 Foxp3 mice compared to their Cre-negative controls are consistent with altered Th1 and Th2 cytokine levels reported in patients with SjD 44,[54][55][56][57][58][64][65][66] .…”
Section: Loss Of Soce In Treg Cells Promotes Th1-and Th2-mediated Inf...supporting
confidence: 77%
“…Increased proportions of HLA-DR + CD8 + T cells were associated with higher disease severity [55] , [56] . Recently, Kaneko et al, reported that infiltrating CD8 + CTLs might induce ductal apoptotic cell death in tissues of patients with Sjogren syndrome [57] . In contrast, we recently reported that infiltrating CD4 + CTLs and CD8 + CTLs might induce apoptotic cell death in tissues of patients with IgG4-RD with preferential targeting of nonendothelial, nonimmune cells of mesenchymal origin by using scRNA-seq techniques [39] .…”
Section: The Pathogenesis Of Sjogren Syndromementioning
confidence: 99%
“…Furthermore, it has been observed that transferring Th17 cells in IL-17 deficient mice restores the SjD disease phenotype, highlighting the key role of Th17 cells in the inflammatory cascade and subsequent disease progression 18 . Recent studies have also highlighted the role of CD8 + T cells within the labial salivary gland infiltrates in SjD patients 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…These cells tend to localize with salivary duct epithelial cells and acinar cells, and their depletion protects against the disease's pathological manifestations 20 .…”
Section: Introductionmentioning
confidence: 99%